Patient Satisfaction and its Relationship to Dental anxiety among patients of Dental Clinics in Baghdad city (Journal Of Educational and Psychological Researches, 2018)
Patient satisfaction and dental anxiety considered as an important factors in dental health care and treatment because they greatly affect the patient's cooperation with the dentist and the extent to which follows the guidelines, treatment and preventive instruction. The present study investigates the relationship between patient satisfaction and dental anxiety, as well as their relation to demographic variables such as gender, age, number of visits, and cultural level. The study was applied on a random sample of dental clinics in Baghdad city with total of (200) patient (108 male and 92 female). Two scales were used in this study, patient satisfaction scale PSS (included 9 aspects, constructed by authors) and Iraqi dental anxiety scale DAS (Salem & Muslim, 2015). The results explained that there is an inverse significant correlation between patient satisfaction and dental anxiety. And there are two demographic variables that have predicted with dental anxiety which are age and number of visits to dental clinic. While there are four aspects of patient satisfaction are predicted to dental anxiety, which are satisfaction of (overall appearance of the clinic, the reception, patient information, and services with safety). The research came out with some of recommendations and suggestions.